Incorporating problem-based learning with direct instruction improves student learning in undergraduate biomechanics. (November 2020) - Wallace, Brian; Knudson, Duane; Gheidi, Naghmeh
Abstract: Problem-based learning (PBL) is based on a 'problem based structure' and may have higher learning efficacy than direct instruction. We quantified PBL on student learning in undergraduate biomechanics. Students (n = 109) at two comprehensive universities in the USA completed the Biomechanics Concept Inventory before and after biomechanics classes that integrated PBL for the seven course topics. Learning increased by 25 ± 14%, which is greater than reported for lecture with low-tech active learning. Eighty-three percent of students "agree(d)" to "strongly agree(d)" PBL was "helpful and effective" at aiding their learning. PBL can be an effective teaching method in undergraduate biomechanics.